Using Stereolithographic Printing to Manufacture Monolithic Microfluidic Devices with an Extremely High Aspect Ratio - Pin-Chuan Chen (MDPI AG, 2021)
Stereolithographic printing (SL) is widely used to create mini/microfluidic devices; however, the formation of microchannels smaller than 500 μm with good inner surface quality is still challenging due to the printing resolution of current commercial printers and the z-overcure error and scalloping phenomena. In the current study, we used SL printing to create microchannels with the aim of achieving a high degree of dimensional precision and a high-quality microchannel inner surface. Extensive experiments were performed and our results revealed the following: (1) the SL printing of microchannels can be implemented in three steps including channel layer printing, an oxygen inhibition process, and roof layer printing; (2) printing thickness should be reduced to minimize the scalloping phenomenon, which significantly improves dimensional accuracy and the quality of inner microchannel surfaces; (3) the inclusion of an oxygen inhibition step is a critical and efficient approach to suppressing the z-overcure error in order to eliminate the formation of in-channel obstructions; (4) microchannels with an extremely high aspect ratio of 40:1 (4000 μm in height and 100 μm in width) can be successfully manufactured within one hour by following the three-step printing process.